2012
DOI: 10.4236/psych.2012.33034
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of a Two-Factor Model of Psychopathy

Abstract: There is currently limited evidence for the two-factor structure of Psychopathy. The aim was to provide evidence for the construct validity of Primary and Secondary Psychopathy. Batteries including the Five Factor Model, the Hogan Development Survey, and Narcissism, Machiavellianism, Empathy, and Aggression, were administered to 241 undergraduate psychology students. Confirmatory factor analysis indicated that a two component structure fitted the data reasonably well (chi-square = 1.939, CFI = .799, RMSEA = .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
2
12
0
1
Order By: Relevance
“…Participants who reported higher levels of psychopathy also reported higher levels of cognitive-perceptual deficits (Hypothesis 1a) and disorganization (Hypothesis 1B). These results are in line with the findings of previous studies (Douglas et al, 2012; that reported positive relationships between secondary psychopathy and positive and disorganized symptoms of schizotypy. At the same time, cognitive-perceptual deficits and disorganization can also be considered as contributors to a psychopathic interpersonal strategy.…”
Section: Discussionsupporting
confidence: 93%
“…Participants who reported higher levels of psychopathy also reported higher levels of cognitive-perceptual deficits (Hypothesis 1a) and disorganization (Hypothesis 1B). These results are in line with the findings of previous studies (Douglas et al, 2012; that reported positive relationships between secondary psychopathy and positive and disorganized symptoms of schizotypy. At the same time, cognitive-perceptual deficits and disorganization can also be considered as contributors to a psychopathic interpersonal strategy.…”
Section: Discussionsupporting
confidence: 93%
“…Openness includes facets that may be consistent with psychopathy—active imagination and a preference for the unusual and novel—but also qualities that are antithetical to psychopathy: openness to feelings, strong impressions to works of art and to beauty, and a willingness to examine and even reconsider one's personal values. Therefore, we expect a negative association between Openness and psychopathy (e.g., Decuyper et al., ; Douglas et al., ).…”
Section: Big Five and Dark Threementioning
confidence: 98%
“…These traits may supplement the FFM traits, in that the FFM explains general dispositional tendencies that apply to most people and interpersonal situations, whereas the DT focuses on less desirable personality traits that are characteristic of people who manipulate and misuse others (Furnham, Richards, & Paulhus, ). The DT traits may, however, be redundant with those traits identified by the FFM, with the result that measures of the facets and global traits of the FFM fully predict the qualities described in the DT (e.g., Brunell, Gentry, Campbell, Hoffman, Kuhnert, & DeMarree, ; Douglas, Bore, & Munro, ; Miller, Lynam, Widiger, & Leukefeld, ).…”
Section: Big Five and Dark Threementioning
confidence: 99%
See 1 more Smart Citation
“…Para estos fines hay, sin embargo, autores que discuten el método de recojo de datos de investigación a través de autoreporte 12 mientras que otros sugieren incluir instrumentos de evaluación para informantes13 .Sobre la diferenciación clínica del concepto Douglas y Bore refieren que Karpman propuso un modelo bifactorial, para aclarar las diferencias entre psicopatía primaria y secundaria. En el primer factor, al cual llamó psicopatía primaria, destacó la insensibilidad hacia los otros, el egoísmo y las actitudes de manipulación; mientras que en el segundo, psicopatía secundaria, estaría caracterizado por alta impulsividad e inestabilidad emocional asociadas a un estilo de vida de auto-fracaso14 .Actualmente las clasificaciones internacionales de trastornos psiquiátricos han establecido criterios diagnósticos específicos aunque utilizando diversas denominaciones para su identificación. La Organización Mundial de la Salud, por ejemplo, en el Capítulo de Enfermedades Mentales de su décima Clasificación Internacional de Enfermedades, lo denomina Trastorno disocial de la personalidad15 .…”
unclassified